FACTORS AFFECTING THE ADOPTION OF MOBILE BANKING: THE CASE OF UNITED BANK ADDIS ABABA CITY CUSTOMERS - Dandena, Serkalem; Timbula, Mekuanint Abera; Mengesha, Tadele (Journal of process management and new technologies, 2019)
Tele Communication Technology now a day has an important impact on a day to day activity of human being in all over the world. One of the bequests drawn from Tele communication technology is Mobile Banking system. The purpose of this study was to identify factors affecting the adoption of mobile banking in Ethiopian Banking industry. The data collected was analyzed using descriptive statistics, correlation and regression analysis. Results are presented using tables, figures, graphs and charts to show the extent of influence of the identified factors on the adoption of mobile banking. The data analysis includes a correlation matrix to test the direction and strength of the study variables against m-banking adoption and regression analysis to examine the extent to which they contribute to adoption of m-banking. The major finding of the study reveals, Technological and Organizational factors from the institutional perspective and customers’ experience and voluntariness of use from customers’ perspective had strong and positive relation with adoption of m-banking. However Gender and Age from the customers view and Environmental factor from the institutions view had a negative relationship with m-banking adoption. The result of the study indicated that Technology and customer’s voluntariness of use had an impact on the adoption of m-banking in greater extent. Therefore, the study recommended that to enhance the m-banking adoption to the required level, United Bank and other banks should invest and deploy on new and “state of the art” technologies with the required human capital and develop a clear strategy to work exhaustively towards the belief of customers to use m-banking system.